Analyzing Compound Structures in Simple Sentences: A Syntactic Study of The Son of Neptune - I Gede Khrisna Andita; Ni Putu Cahyani Putri Utami (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This study explores the syntactic structures of simple sentences containing compound subjects and compound predicates in Rick Riordan’s The Son of Neptune. Although often perceived as grammatically minimal, simple sentences in literary texts can exhibit internal complexity through the use of coordinated grammatical elements. Rather than employing constituent-based analysis, this research adopts a type-based syntactic approach to classify coordinated structures within single independent clauses. The analysis draws upon the syntactic models of Quirk and Greenbaum (1973) and Brown and Miller (1991), which provide a functional framework for identifying core syntactic components. A qualitative descriptive method was applied to 100 simple sentences, each categorized into one of three structural types: those with compound subjects only, compound predicates only, or both. The results suggest that compound predicates appear more frequently than compound subjects, reflecting the novel’s emphasis on dynamic, action-oriented narration. The study concludes that syntactic coordination within structurally simple yet syntactically rich sentences supports clarity and variation in narrative expression. This syntactic approach may also be applied as a teaching framework for analyzing literary texts.